pemikiran filosof Ibnu Rusyd tentang eskatologi - Fitria Rika Susanti; Surma Hayani (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2021)
The Day of Resurrection is one of the pillars of faith that is believed by the majority of Muslims. Ibn Rushd did the same, but he had the view that in the afterlife there would only be spiritual awakening. This is different from the thoughts of theologians who hold fast means lafzi from the verses of the Qur'an and Sunnah which states that the resurrection in the hereafter will be both physical and spiritual. From the philosophers' thoughts arise various understandings of opinion in discussing the day of human resurrection in the afterlife. This type of research is the library (library research) while there are two sources of research data, namely primary data sources and secondary data sources. Primary data sources were taken from Ibn Rushd's book, namely: Tahâfut At-Tahâfut, secondary data sources were taken from books, research reports, papers, scientific journals related to this research. The results of this study, according to Ibnu Rusyd, eschatology is the science of the resurrection in the afterlife. Ibn Rushd's argument about the resurrection in the afterlife is spiritual or spiritual. So what will be resurrected is the soul, while the body that has disappeared will not be resurrected because the soul (soul) is eternal and eternal. The form of resurrection in the afterlife is a spiritual form, not physical or corpse, because the one who will receive merit and punishment is spiritual.